Human Rights Defenders in Indonesia's Digital Age: Navigating Limited Spaces in the Quest for Digital Democracy - Rahayu Rahayu; Kholis Roisah; Khansadhia Afifah Wardana; Vania Lutfi Safira Erlangga (Sriwijaya Law Review, 2024)
The enactment and application of the Electronic Transaction Information Law are pivotal for delineating the appropriate boundaries for exercising freedom of opinion and expression within Indonesia's digital sphere. According to reports from international digital rights research and advocacy organizations, online media journalists and human rights activists frequently encounter direct pressure and cyber harassment. This article explores the balance of freedom of expression in Indonesia's digital domain to ensure a secureenvironment for human rights defenders advocating for human rights. This study uses socio- legal methodologies to draw on data from literature reviews and in-depth interviews. It underscores the need for regulatory reforms to define prohibited hate speech explicitly. SAFENet documented 153 cyber-attacks in Indonesia in 2022, predominantly targeting civil society groups, students, activists, and journalists. Additionally, the National Committee on Human Rights reported that 52% of attacks on human rights defenders occurred in the digital realm. While the protection of digital democracy varies by nation, Indonesia must establish aninstitution responsible for properly enforcing the ITE Law alongside an independent monitoring mechanism and related policies. Such institutions, including those dedicated to human rights defenders, uphold human rights and demonstrate a commitment to the principles of freedom, respect, equality, and dignity within society.